Nanoparticles as Potential Agents of Chemical and Biological Weapons - Ján Lakota (Вестник войск РХБ защиты)
The wide distribution in industry, medicine, agriculture, and other areas of human activity of nanoscale objects raise the question of the possibility of their dual use, which in this work means the use for deliberate mass destruction of people. The aim of the work is to consider nanoparticles as potential agents of chemical and biological weapons. Nanoparticles of any type have been shown to have biological activity. This is due to an increase in the surface activity of particles during the transition from microscale to nanoscale and their ability to penetrate the cell, especially cell nucleus. Being non-biological objects, interacting with cell receptors, distorting intracellular signaling pathways and affecting the genetic regulation of the cell, they can cause a variety of pathological effects (oxidative stress, neuroinflammation, neurodegeneration, etc.). Therefore, with the transition from microscales to nanoscales, essentially remaining chemical compounds, particles of non-toxic materials can transform into potential biological and chemical damaging agents. The existing possibilities of their mass use through the respiratory system, skin, gastrointestinal tract and through the introduction of injectable forms of drugs suggest that based on damaging agents of this type, weapons of mass destruction of a new type that are not subject to the Conventions on the Prohibition of Chemical and Biological Weapons can be developed. It is necessary to start developing methods for detecting nanoparticles and other nanoobjects in various environments surrounding a person, food and dosage forms